алгебра 7 класс

Номер 973

Условие:

Упростите выражение:
а) (а + 2)(а - 2) - а(а - 5);           б) (а - 3)(3 + а) + а(7 - а);
в) (b - 4)(b + 4) - (b - 3)(b + 5);  г) (b + 8)(b - 6) - (b - 7)(b + 7);
д) (с - 1)(с + 1) + (с - 9)(с + 9);  е) (5 + с)(с - 5) - (с - 10)(с + 10).

 

Ответ:

а) (а + 2)(а - 2) - а • (а - 5) = a2 - 4 - a2 + 5a = 5a - 4;
б) (а - 3)(3 + а) + а • (7 - а) = a2 - 9 + 7a - a2 = 7a - 9;
в) (b - 4)(b + 4) - (b - 3)(b + 5) = b2 - 16 - b2 - 5b + 3b + 15 = -2b - 1;
г) (b + 8)(b - 6) - (b - 7)(b + 7) = b2 - 6b + 8b - 48 - b2 + 49 = 2b + 1;
д) (с - 1)(с + 1) + (с - 9)(с + 9) = c2 - 1 + c2 - 81 = 2c2 - 82;
е) (5 + с)(с - 5) - (с - 10)(с + 10) = c2 - 25 - c2 + 100 = 75.

share with Whatsapp
share with Telegram
powered by social2s